2020
DOI: 10.1177/0044118x20942248
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Background and Crime Among Young People: An Examination of the Importance of Delinquent Friends Based on National Self-Report Data

Abstract: In this article we examine whether different agents of socialization—family, school, and peers—are differentially associated with offending among different immigrant groups. Our expectation is to find that the association between delinquent friends and offending is stronger for first- and second-generation immigrants than for youths of native Swedish background. We use data from four nationally representative self-report studies of 21,504 adolescents with an average age of 15 years in Sweden. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For instance, some studies based on self-reported delinquency in Europe found that immigrant youths had either similar or lower crime prevalence rates compared to the native population ( Junger-Tas, 1997 ; Torgersen, 2001 ). Other studies conducted in northern European countries, on the other hand, revealed higher rates of violent delinquency in second-generation immigrants in Germany ( Enzmann et al, 2010 ), Switzerland ( Killias et al, 2010 ; Ribeaud and Eisner, 2010 ) and Sweden ( Svensson and Shannon, 2020 ). In Norway, a study found some differences in patterns of self-reported delinquency amongst adolescents with respect to immigrant status, gender and country of origin ( Torgersen, 2001 ).…”
Section: Prior Research On Juvenile Delinquency Using Self-reported Datamentioning
confidence: 93%
“…For instance, some studies based on self-reported delinquency in Europe found that immigrant youths had either similar or lower crime prevalence rates compared to the native population ( Junger-Tas, 1997 ; Torgersen, 2001 ). Other studies conducted in northern European countries, on the other hand, revealed higher rates of violent delinquency in second-generation immigrants in Germany ( Enzmann et al, 2010 ), Switzerland ( Killias et al, 2010 ; Ribeaud and Eisner, 2010 ) and Sweden ( Svensson and Shannon, 2020 ). In Norway, a study found some differences in patterns of self-reported delinquency amongst adolescents with respect to immigrant status, gender and country of origin ( Torgersen, 2001 ).…”
Section: Prior Research On Juvenile Delinquency Using Self-reported Datamentioning
confidence: 93%